Biofilm detachment by self-collapsing air microbubbles : a potential chemical-free cleaning technology for membrane biofouling - Agarwal, Ashutosh (2013)
Microbubbles (MBs) have been known for their ability to generate pressure waves through shrinking and subsequent self-collapsing phenomenon. In the present study, we have investigated the potential of air MBs for biofilm detachment from a nylon membrane surface in comparison to chemical cleaning by sodium hypochloride (NaOCl). About 88% of fixed biomass detachment was observed after 1 h air microbubbling, while only 10% of biofilm detachment was achieved in the control experiment without microbubbles. Images taken with a confocal laser scanning microscope (CLSM) clearly showed that nearly all extracellular polysaccharides and proteins in biofilms were removed from the membrane surface, indicating a complete disruption of the extracellular polymeric matrix of biofilms. It was further demonstrated that microbubbling is much more efficient than chemical cleaning with 0.5% NaOCl solution in terms of removal of fixed biomass and extracellular polysaccharides and proteins. This study provides experimental evidence showing that self-collapsing air MBs is a chemical-free and eco-friendly technology for biofilm detachment.